Performance Analysis of Piezoelectric Energy Harvesting in Pavement: Laboratory Testing and Field Simulation. Issue 3 (March 2019) - Jasim, Abbas F.; Wang, Hao; Yesner, Greg; Safari, Ahmad; Szary, Pat
This study investigated the energy harvesting performance of a piezoelectric module in asphalt pavements through laboratory testing and multi-physics based simulation. The energy harvester module was assembled with layers of Bridge transducers and tested in the laboratory. A decoupled approach was used to study the interaction between the energy harvester and the surrounding pavement. The effects of embedment location, vehicle speed, and temperature on energy harvesting performance were investigated. The analysis findings indicate that the embedment location and vehicle speed affects the resulted power output of the piezoelectric energy harvesting system. The embedment depth of the energy module affects both the magnitude and frequency of stress pulse on top of the energy module induced by tire loading. On the other hand, higher vehicle speed causes greater loading frequency and thus greater power output; the effect of pavement temperature is negligible. The analysis of total power output before reaching fatigue failure of the energy module can be used to determine the optimum embedment location in the asphalt layer. The proposed energy harvesting system provides great potential to generate green energy from waste kinetic energy in roadway pavements. Field study is recommended to verify these findings with long-term performance monitoring of pavement with embedded energy harvesters.